THE FUTURE INFORMATION SOCIETY : Social and Technological Problems - Hofkirchner, Wolfgang, 1953- , editor; Burgin, M. S. (Mark Semenovich) , editor (New Jersey : World Scientific Publishing, 2017)
Includes bibliographical and references